Insect Attraction Associated with Oryza sativa L. on Trap Color Variation in Tountimomor Village, West Kakas District, Minahasa Regency - Susanti Mangansige; Elisabet R.M. Meray; Wilson Moniaga; Ameilia Zuliyanti Siregar (Talenta Publisher, 2024)
Rice is an important food crop as the main source of carbohydrates. In Tountimomor Village, West Kakas Subdistrict, Menado, Northern Sulawesi which detection of rice production is disrupted by pest attacks. This study aims to evaluate the effectiveness of color traps in attracting insects on rice plants as an alternative environmentally friendly control. Using a Randomized Group Design (RAK) with 4 treatments (yellow, blue, red, and transparent/control traps), each trap was set on 5 plots. Trapped insects were identified in the laboratory. Results showed yellow traps were most effective with an average of 59 insects, followed by blue (42.4) and red (28.6). Color traps can be an effective and safe insect control solution in paddy plantations in Menado.